Islamophobic rhetoric in the wake of the Orlando mass killing - Mohamed Ali, Haja Mohideen; Haja Mohideen, Shamimah (International Journal of Arts Humanities and Social Sciences, 2016)
The paper seeks to identify Islamophobic terms which are directed at Islam and Muslims in a highly pejorative manner. The data was collected from www.yahoo.com/news/us for a duration of one week following the massacre of nearly 50 members of the LGBT community in a gay club in Orlando, Florida, by a single radicalized Muslim of Afghan descent. Articles related to the tragic incident which appeared in the above mentioned website were perused for Islamophobic language. It was found that there is a tendency to overgeneralize Islam and its followers on the basis of the actions of a few radicalized individuals and organizations which abused Islam by their activities which were not condoned by the religion. The lexical collocation of words including Islam and other religious terms were used without a proper understanding of what they really meant and showed much bias towards Islam and its followers.